2021
DOI: 10.9778/cmajo.20200064
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adverse childhood experiences among individuals aged 45 to 85 years: a cross-sectional analysis of the Canadian Longitudinal Study on Aging

Abstract: Background: Population-level prevalence estimates for a broad range of adverse childhood experiences (ACEs), which are known to affect health across the lifespan, are currently unavailable in Canada. The purpose of this study was to estimate the prevalence of individual ACEs by sociodemographic factors among middle-aged and older adults.Methods: Data for this cross-sectional analysis were obtained from the first follow-up (2015-2018) of the Canadian Longitudinal Study on Aging (baseline recruitment from 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
3
13
0
1
Order By: Relevance
“…The distribution of ACEs in our sample was similar to the recently reported prevalence of ACEs in the complete CLSA cohort, which includes both the in-person (i.e., comprehensive) and telephone (i.e., tracking) cohorts ( n = 44,817) [32], and consistent with the prevalence of childhood maltreatment reported in earlier Canadian population-based studies [15]. Similar to these studies, we found that younger age groups reported higher prevalence of all ACE types, except parental death, which was more prevalent in older age groups.…”
Section: Discussionsupporting
confidence: 81%
“…The distribution of ACEs in our sample was similar to the recently reported prevalence of ACEs in the complete CLSA cohort, which includes both the in-person (i.e., comprehensive) and telephone (i.e., tracking) cohorts ( n = 44,817) [32], and consistent with the prevalence of childhood maltreatment reported in earlier Canadian population-based studies [15]. Similar to these studies, we found that younger age groups reported higher prevalence of all ACE types, except parental death, which was more prevalent in older age groups.…”
Section: Discussionsupporting
confidence: 81%
“…From the full dataset, the average ACEs score among individuals was close to 3 ACEs exposures, with over 80% of the full dataset to have reported exposure to at least 1 ACEs. This is somewhat higher than recent longitudinal estimates based on over 40,000 participants from the Canadian Longitudinal Study on Aging where 61.6% of participants reported exposure to at least 1 ACEs ( Joshi et al, 2021 ). The higher exposure to ACEs in the current study reported could be due to variations in the types of ACEs captured as well as the different ages of the sample affecting recall to childhood events.…”
Section: Discussionmentioning
confidence: 54%
“…In the present clinic-referred sample, multisource assessment of a much broader array of negative event categories found that 90% had experienced at least one negative event. This compares with very large community retrospective self-report samples, where 61% of Canadians ( n > 44,000; Joshi et al, 2021) and 55% of Americans ( n > 48,000; Campbell et al, 2016) reported one ACE (Campbell et al [2016] summarized the range of those reporting at least one ACE in numerous community sample surveys as 46.4% to 79.5%). As our clinic sample contained only a small portion of youth who had turned 18, we must emphasize that all estimates of adversity (i.e., ALEIC total score) reported here are underestimates of total childhood prevalence, as many years of possible exposure had yet to be lived.…”
Section: Discussionmentioning
confidence: 81%
“…This compares with very large community retrospective self-report samples, where 61% of Canadians (n . 44,000; Joshi et al, 2021) and 55% of Americans (n . 48,000; Campbell et al, 2016) reported one ACE (Campbell et al [2016] summarized the range of those reporting at least one ACE in numerous community sample surveys as 46.4% to 79.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation